Assignment of two loci for autosomal dominant adolescent idiopathic scoliosis to chromosomes 9q31.2-q34.2 and 17q25.3-qtel. Issue 2 (11th October 2007) - Ocaka, L; Zhao, C; Reed, J A; Ebenezer, N D; Brice, G; Morley, T; Mehta, M; O'Dowd, J; Weber, J L; Hardcastle, A J; Child, A H
Abstract : Background: Adolescent idiopathic scoliosis (AIS) is the most common form of spinal deformity, affecting up to 4% of children worldwide. Familial inheritance of AIS is now recognised and several potential candidate loci have been found. Methods: We studied 25 multi-generation AIS families of British descent with at least 3 affected members in each family. A genomewide screen was performed using microsatellite markers spanning approximately 10-cM intervals throughout the genome. This analysis revealed linkage to several candidate chromosomal regions throughout the genome. Two-point linkage analysis was performed in all families to evaluate candidate loci. After identification of candidate loci, two-point linkage analysis was performed in the 10 families that segregated, to further refine disease intervals. Results: Significant linkage was obtained in a total of 10 families: 8 families to the telomeric region of chromosome 9q, and 2 families to the telomeric region of 17q. A significant LOD score was detected at marker D9S2157 Zmax = 3.64 (θ = 0.0) in a four-generation family (SC32). Saturation mapping of the 9q region in family SC32 defined the critical disease interval to be flanked by markers D9S930 and D9S1818, spanning approximately 21 Mb at 9q31.2-q34.2. In addition, seven other families segregated with this locus on 9q. In two multi-generation families (SC36 and SC23) not segregating with the 9q locus, a maximum combined LOD score of Zmax = 4.08 (θ = 0.0) was obtained for marker AAT095 on 17q. Fine mapping of the 17q candidate region defined the AIS critical region to be distal to marker D17S1806, spanning approximately 3.2 Mb on chromosome 17q25.3-qtel. Conclusion: This study reports a common locus for AIS in the British population, mapping to a refined interval on chromosome 9q31.2-q34.2 and defines a novel AIS locus on chromosome 17q25.3-qtel.